2015
DOI: 10.4187/respcare.04028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Very-High-Flow Nasal Therapy on Airway Pressure and End-Expiratory Lung Impedance in Healthy Volunteers

Abstract: BACKGROUND: Previous research has demonstrated a positive linear correlation between flow delivered and airway pressure generated by high-flow nasal therapy. Current practice is to use flows over a range of 30 -60 L/min; however, it is technically possible to apply higher flows. In this study, airway pressure measurements and electrical impedance tomography were used to assess the relationship between flows of up to 100 L/min and changes in lung physiology. METHODS: Fifteen healthy volunteers were enrolled int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
131
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 18 publications
10
131
1
Order By: Relevance
“…Underscoring this point, we note that change in end-expiratory lung impedance (and thus end-expiratory lung volume) was widely variable, suggesting either a limitation of technique or that the relationship between flow and end-expiratory lung volume may be more complicated then assumed. The latter possibility appears to be supported by the analysis of the P aO 2 /F IO 2 data from Vargas et al 10 Applying the estimate (10 L/min flow ϭ 1.2 cm H 2 O) of Parke et al 11 to the subjects in Vargas' study with flow fixed at 60 L/min in all subjects, one would expect an airway pressure of between 5 and 7 cm H 2 O. If this were to correlate with PEEP at the alveolus, as has been implied in previous studies, it would not be unreasonable, using a conservative interpretation of such estimates, to expect a comparable improvement in oxygenation in both the 60 L/min HFNC group and the NIV group receiving 5 cm H 2 O CPAP.…”
Section: In Support Of Hfnc For Acute Respiratory Failuresupporting
confidence: 52%
See 2 more Smart Citations
“…Underscoring this point, we note that change in end-expiratory lung impedance (and thus end-expiratory lung volume) was widely variable, suggesting either a limitation of technique or that the relationship between flow and end-expiratory lung volume may be more complicated then assumed. The latter possibility appears to be supported by the analysis of the P aO 2 /F IO 2 data from Vargas et al 10 Applying the estimate (10 L/min flow ϭ 1.2 cm H 2 O) of Parke et al 11 to the subjects in Vargas' study with flow fixed at 60 L/min in all subjects, one would expect an airway pressure of between 5 and 7 cm H 2 O. If this were to correlate with PEEP at the alveolus, as has been implied in previous studies, it would not be unreasonable, using a conservative interpretation of such estimates, to expect a comparable improvement in oxygenation in both the 60 L/min HFNC group and the NIV group receiving 5 cm H 2 O CPAP.…”
Section: In Support Of Hfnc For Acute Respiratory Failuresupporting
confidence: 52%
“…Parke et al 12 had previously described a linear correlation between flow and airway pressure in HFNC up to the currently accepted maximum rate of 60 L/min. Here, 11 they increased flow up to as much as 100 L/min in healthy volunteers and quantified the correlation between flow rate and nasopharyngeal PEEP at about 1 cm H 2 O nasopharyngeal PEEP increment for each 10 L/ min of flow, up to a maximum of 8 -12 cm H 2 O at 100 L/ min.…”
Section: In Support Of Hfnc For Acute Respiratory Failurementioning
confidence: 99%
See 1 more Smart Citation
“…(12), this fact may be related to both effective supply of oxygen and other mechanisms, such as apnoeic ventilation (19)(20)(21). In addition, during pre-oxygenation with HFNO, end expiratory lung volume and FRC increased and dead space decreased (18,(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most patients included in studies have bilateral infiltrates [20,32]. The Berlin definition of ARDS [34] requires a minimum of 5 cmH 2 O of PEEP, and it has been shown that HFNC can provide a level of PEEP that is higher at peak expiratory pressure [7]. Moreover, ARDS does not begin at the time of mechanical ventilation onset.…”
Section: Ards Patientsmentioning
confidence: 99%